Musical Exotica and Nostalgia: 'Localizing' Malaysian Music Video? - Tan Sooi Beng, (Wacana Seni Journal of Arts Discourse, 2003)
Music video has become an essential component of the music recording industry. Introduces in the 1980s as a promotional strategy, music video helps audiences to identify with the artist's personality including more subtle ones such as a sense of humour or taste in clothes, friends, spouses and visual images' (Riordan 1991: 311). Today, virtually every single release by both majors and independents is supported by a video. The single song in the video has become a crucial factor in the marketing of an album. The success of stars such as Madonna, Duran-Duran and Paula Abdul has been attributed to their music videos.